STUDY EXPLORATION THEMATIC LEARNING BASED ON LOCAL WISDOM of CENTRAL JAVA on FOURTH GRADE of ELEMENTARY SCHOOL - Priskila Dwinando Marindasari; Sri Marmoah; Sri Yamtimah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This study aims to obtain a description of knowledge about thematic learning based on local wisdom of Central Java in fourth grade elementary school students. The type of this research is descriptive research. The study was conducted through field studies to obtain a picture of the knowledge of teachers and learners about thematic learning based on local wisdom of Central Java in fourth grade elementary school students. The results showed that in general the teacher of fourth grade of elementary school in Surakarta had not fully taught local wisdom of Central Java in thematic learning. Teachers are more focused on teaching the material on student books. Some teachers expect training to design and create learning that is capable of developing cognitive, affective, and psychomotor abilities and can introduce local wisdom of Central Java for learners. While learners expect an interesting source of learning and able to make them learn independently. At the same time can recognize local wisdom in the area.